Dampak Pandemi Covid-19 Terhadap Pasar Saham Di Indonesia - Henny Saraswati (JAD : Jurnal Riset Akuntansi & Keuangan Dewantara, 2020)
This study aims to determine the factors that can affect financial distress in food and beverage companies listed on the Indonesia Stock Exchange in 2014-2018. The factors used are the size of the hood and financial distress.This type of research is an associative causal research with an ex post facto approach. Samples were taken using purposive sampling technique. A sample of 34 companies from 168 food and beverage companies listed on the Indonesia Stock Exchange in 2014-2018, so that the analyzed research data amounted to 170. The data analysis techniques used were descriptive statistics and logistic regression.The results of this study indicate that (1) Profit has no significant effect on predicting financial distress conditions. (2) Cash flow has no effect in predicting financial distress conditions. (3) Leverage has no effect in predicting financial distress conditions. And simultaneously this study states that earnings, cash flow and leverage do not affect predicting financial distress.